Restoration Strategy for Urban Power Distribution Systems Considering Coupling with Transportation Networks Under Heavy Rainstorm Disasters - Dongli Jia; Zhao Li; Yongle Dong; Xiaojun Wang; Mingcong Lin; Kaiyuan He; Xiaoyu Yang; Jiajing Liu (Energies)
With the increasing frequency of extreme weather events such as heavy rainstorm disasters, the stable operation of power systems is facing significant challenges. This paper proposes a two-stage restoration strategy for the distribution networks (DNs). First, a grid-based modeling approach is developed for urban DNs and transportation networks (TNs), capturing the dynamic evolution of heavy rainstorm disasters and more accurately modeling the impact on TNs and DNs. Then, a two-stage restoration strategy is designed for the DN by coordinating soft open points (SOPs) and mobile energy storage systems (MESSs). In the disaster progression stage, SOPs are utilized to enable the flexible reconfiguration and islanding of the DN, minimizing load loss. In the post-disaster recovery stage, the MESS and repair crew are optimally dispatched, taking into account the state of the TN to expedite power restoration. Finally, the experimental results demonstrate that the proposed method reduces load loss during restoration by 8.09% compared to approaches without precise TN and DN modeling.